Defining the Asthma-COPD Overlap Syndrome in a COPD Cohort - Cosio, Borja G; Soriano, Joan B; López-Campos, Jose Luis; Calle-Rubio, Myriam; Soler-Cataluna, Juan José; de-Torres, Juan P; Marín, Jose M; Martínez-Gonzalez, Cristina; de Lucas, Pilar; Mir, Isabel; Peces-Barba, Germán; Feu-Collado, Nuria; et al. (Chest, 2016)
Asthma-COPD overlap syndrome (ACOS) has been recently described by international guidelines. A stepwise approach to diagnosis using usual features of both diseases is recommended although its clinical application is difficult. To identify patients with ACOS, a cohort of well-characterized patients with COPD and up to 1 year of follow-up was analyzed. We evaluated the presence of specific characteristics associated with asthma in this COPD cohort, divided into major criteria (bronchodilator test > 400 mL and 15% and past medical history of asthma) and minor criteria (blood eosinophils > 5%, IgE > 100 IU/mL, or two separate bronchodilator tests > 200 mL and 12%). We defined ACOS by the presence of one major criterion or two minor criteria. Baseline characteristics, health status (COPD Assessment Test [CAT]), BMI, airflow obstruction, dyspnea, and exercise capacity (BODE) index, rate of exacerbations, and mortality up to 1 year of follow-up were compared between patients with and without criteria for ACOS. Of 831 patients with COPD included,125 (15%) fulfilled the criteria for ACOS, and 98.4% of them sustained these criteria after 1 year. Patients with ACOS were predominantly male (81.6%), with symptomatic mild to moderate disease (67%), who were receiving inhaled corticosteroids (63.2%). There were no significant differences in baseline characteristics, and only survival was worse in patients with non-ACOS COPD after 1 year of follow-up (P < .05). The proposed ACOS criteria are present in 15% of a cohort of patients with COPD and these patients show better 1-year prognosis than clinically similar patients with COPD with no ACOS criteria. ClinicalTrials.gov; No.: NCT01122758; URL: www.clinicaltrials.gov.